Combined experimental-theoretical study of electron mobility-limiting mechanisms in SrSnO3 - Tristan K. Truttmann (Nature Portfolio, 2021)
Semiconductor research is undergoing transformative changes thanks to the discovery and development of novel materials. The authors disclose the role of electron-phonon interaction and impurity scattering in a novel ultrawide bandgap perovskite oxide, paving the way for new applications in high-power electronics.